2023
DOI: 10.1097/sla.0000000000005809
|View full text |Cite
|
Sign up to set email alerts
|

Recurring Pancreatic Neuroendocrine Tumor: Timing and Pattern of Recurrence and Current Treatment

Abstract: Objective: The objective of this study was to describe the pattern of recurrence, treatments received, as well the oncological outcomes, of pancreatic neuroendocrine tumors (PanNETs) following curative surgery. Background: PanNETs recur in 10% to 15% of cases following surgery. Information on the natural history and management of recurring disease is lacking. Materials and Methods: Patients with PanNET that underwent curative surgery at 4 institutions between 2000 and 2019 were identified. Patients with poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This finding differs from what has been observed in large population studies 1,2,6 that showed an association between older age and shorter overall survival. However, most patients with localized PanNET undergoing surgery have low-grade indolent neoplasms experiencing long survival even after recurrence 15,16 . For patients with PanNET, the cause of death may not be related to neuroendocrine disease, 17 so we focused on disease-specific survival, removing possible biases related to the association between age and other causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…This finding differs from what has been observed in large population studies 1,2,6 that showed an association between older age and shorter overall survival. However, most patients with localized PanNET undergoing surgery have low-grade indolent neoplasms experiencing long survival even after recurrence 15,16 . For patients with PanNET, the cause of death may not be related to neuroendocrine disease, 17 so we focused on disease-specific survival, removing possible biases related to the association between age and other causes of death.…”
Section: Discussionmentioning
confidence: 99%